Entry Strategies in Business Process Offshoring. (November 2013) - Luo, Yadong; Jayaraman, Vaidyanathan
Business process offshoring (BPO) has emerged as an important strategy and a prevalent landscape in global service operations management. As one of the first attempts to analyze this challenging issue in an emerging market, this study examines how firms develop a set of global expansion strategies, including where (location), when (timing), and what (diversification), that are unique to BPO service operations. Our analysis of 424 BPO service operations centers in India demonstrates that BPO units with greater knowledge specialization tend to operate in more developed cities and that information connectivity, government support, and human resources competitiveness are critical locational determinants. Although BPO investment is less path dependent than traditional foreign direct investment, behavioral variables, such as assertiveness and pre-BPO experience in the host locations, are important factors behind the timing decision. Finally, BPO units involving lower knowledge specialization or higher process measurability are more diversified in terms of the number of business processes outsourced.